2018
DOI: 10.1108/arj-06-2015-0077
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-performing loans in banking sector in small developing island states

Abstract: Purpose The banking sector stability depends in large part on the size of non-performing loans (NPLs). Hence, the factors which explain the problem loans are very useful information for banks. Notably, studies in this regard with respect to the small developing countries’ banking sector have received less attention. Therefore, this study aims to examine the determinants of NPLs with a case of Fiji’s banking sector, over the period 2000-2013. Design/methodology/approach The balanced sample consists of the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
3
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
2
25
3
9
Order By: Relevance
“…If the bank has a low BOPO that shows operational activities have been efficient, the bank will have the opportunity to get optimal profits, increase the number of loans extended, and improve services to customers to reduce bank credit risk. However, this result differs from the research of Argaw [14] Rachman [16], and Kumar [23], which shows that BOPO does not affect NPL.…”
Section: Resultscontrasting
confidence: 99%
“…If the bank has a low BOPO that shows operational activities have been efficient, the bank will have the opportunity to get optimal profits, increase the number of loans extended, and improve services to customers to reduce bank credit risk. However, this result differs from the research of Argaw [14] Rachman [16], and Kumar [23], which shows that BOPO does not affect NPL.…”
Section: Resultscontrasting
confidence: 99%
“…Next, Ikram et al (2016) and Asfaw et al (2016) have identified some behavioral factors of NPLs such as type of collateral, quantity of collateral, credit assessment, lack of proper monitoring, poor credit culture, grace period of credit repayment, creditors' behavior, repayment flexibility, credit policies, tenure of loans, etc. Moreover, Kumar et al (2018) find that bad management is a triggering factor of NPLs. Again, Novellyni and Ulpah (2017) find that moral hazard has a positive significant impact on NPLs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The research was done during 2000-2013 by taking a sample of five commercial banks and two nonbank financial institutions. This study uses the ordinary least square analysis model, random effects, and fixed effects regression methods (Kumar et al, 2015).…”
Section: Previous Studymentioning
confidence: 99%